Community structure of anurans along an altitudinal gradient: the role of topographic and climatic variables and their implications for conservation - Matavelli, Rodrigo Augusto (2019)
Montane ecosystems cover approximately 22 to 25% of land surface from sea level to more than 8,000 m a.s.l., harboring more than a third of the planet\'s biodiversity and includ half of global biodiversity hotspots. Among geographical gradients (latitudinal or altitudinal), the latitudinal species richness pattern is the most recognized and studied. Although not so intensively studied as latitudinal gradients, altitudinal gradients also provide great patterns of species richness distributions. Despite of the processes that driving the species richness patterns are still poorly understood, three main patterns have been reported along altitudinal gradients: 1) decreasing of species richness with increasing altitude, 2) increase in species richness with increased altitude, and 3) increasing species richness at intermediate altitudes (hump-shaped pattern), followed by a decreasing of species richness with increasing altitude. The hump-shaped pattern is considered the most common. A macroecological hypothesis that to explain species richness patterns along geographical gradients focusing in species range size is Rapoport\'s rule. This rule is a positive correlation between altitude and species range size distribution based on climate seasonality effects. Rapoport\'s rule prediz that species that can withstand broad climatic variability can become more widely distributed along geographical gradients. However, this hypothesis still has presented controversial results and this controversial results increased our interest in testing Rapoport\'s altitudinal rule in Atlantic Forest mountain ecosystems biome. However, patterns and process that drivres community assembly along altitudinal gradients have received little attention and remain controversial. Based on the anuran community strutucture variation (richness, composition and abundance) along altitudinal gradients, the present work aims to understand and disentangle the topographic and climatic effects on spatial patterns distribution and species altitudinal range size in the Atlantic Forest highlands, which will highlight how topographic and climate conditions acting in communities\' assembly along altitudinal gradients subside important rules to biodiversity conservation.